The relationship between safety management practices and safety performance in University of Malaya Medical Centre - Nurul Hafizah Kamaliah, Mohd Jamil (2019)
Safety management practices play a vital role in reducing accident in the workplace by improving working conditions and positively influence both employers and employee’s performance towards safety and health. This study examined the perception of clinical nurses in University of Malaya Medical Centre located in Lembah Pantai, Kuala Lumpur on four safety management practices namely management commitment, safety training, workers’ participation and safety communication and feedback with safety performance using questionnaires among 210 nurses. A cross-sectional study design was conducted using cluster sampling technique. Descriptive statistics, reliability test, Pearson Correlation and Multiple Correlation were used to analyse the data. Data analysed from this study revealed that Management Commitment, Safety Training, Workers’ Participation and Safety Communication and Feedback are factors that have significant correlation with Safety Performance. Safety Training and Safety Communication and Feedback have significant influence towards Safety Performance. Management Commitment and Workers’ Participation do not have significant influence on Safety Performance in this organization even though they have a significant correlation. Understanding the dimensions of safety management practices that can influence safety performance in the hospital organization is the first step before further developing effective strategies to manage the safety and health problems. Enforcement of policies, establishing a continuous training program, strengthening the management commitment and encouraging workers participation in safety could enhance workplace safety especially among clinical nurses.